Unraveling the impact of nitrogen nutrition on cooked rice flavor and texture - Champagne, Elaine T.; Bett-Garber, Karen L.; Thomson, Jessica L.; Fitzgerald, Melissa A. (Wiley, 2009)
Understanding the influences of amylose and protein contents on rice sensory properties is key to maintaining quality and providing consumers with rice with desired flavor and textural attributes. This research focused on delineating the effects of nitrogen nutrition on cooked rice texture and flavor. The sensory properties of cultivars grown in adjoining fields with differing rates of nitrogen fertilizer (to yield grains with a large spread in protein contents) were measured by a panel trained in descriptive analysis. Second, rice sensory properties were modeled using apparent amylose and protein data. Fertilizer level affected protein and apparent amylose contents and, in turn, cooked rice texture. Protein contents were significantly higher (P < 0.0007) and apparent amylose contents were significantly lower (P < 0.0001) at the higher fertilizer level. Models revealed a negative correlation of protein content with initial starchy coating, slickness, and stickiness between grains—three attributes that are perceived when cooked rice is first introduced into the mouth. Models for roughness, hardness, and moisture absorption—attributes representing three phases of evaluation in the mouth—showed a positive correlation with protein content. The models provide insight into the magnitude of change in protein content that is likely required to observe textural changes in cooked rice.